Penerapan Layanan Konseling Individu dalam Meningkatkan Kepercayaan Diri Siswa dengan Teknik Client-centered di SMP Frater Don Bosco Tomohon: Penelitian - Simangunsong, Anggi Innocensia; Mangantes, Meisie L.; Kasenda, Rinna Y. (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to improve students’ self-confidence through the implementation of individual counseling services with client-centered techniques. The background of this study is based on the fact that there are still students who experience low self-confidence, which impact the learning process and social interactions of students both outside and inside the school environment. This study uses the PTBK approach or counseling guidance action research carried out in two cycles. Each activity consists of the planning, implementation, observation, and reflection stages. The subject of this study was a junior high school student who showed problems with low self-confidence. The instruments used in this study were interview guidelines, observations, and self-confidence questionnaires. The results of this study indicate that in the first cycle, the level of self-confidence of the counselee was in the moderate category, while in the second cycle, it experienced a significant increase to the high category. These findings indicate that individual counseling services using client-centered techniques are effective in improving students’ self confidence.